Bacterial diversity using metagenomics of 16s rDNA in water kefir, an innovative source of probiotics for bee nutrition - Rodríguez, María A. (2024)
Water kefir is a sparkling, slightly acidic fermented beverage made from sugar, water,and water kefir grains, which are a mixture of yeast and bacteria. These grains produce a varietyof fermentation compounds such as lactic acid, acetaldehyde, acetoin, ethanol and carbondioxide. In this study, a high-throughput sequencing technique was used to characterize thebacterial composition of the original water kefir from which potential probiotics were obtained.We studied the bacterial diversity of both water kefir grains and beverages. DNA was extractedfrom three replicate samples of both grains and beverages using the Powerlyzer Microbial Kit.The hypervariable V1---V2 region of the bacterial 16S ribosomal RNA gene was amplified toprepare six DNA libraries. Between 1.4 M and 2.4 M base-pairs were sequenced for the library.In total, 28 721 971 raw reads were obtained from all the samples. Estimated species richnesswas higher in kefir beverage samples compared to grain samples. Moreover, a higher level ofmicrobial alpha diversity was observed in the beverage samples. Particularly, the predominantbacteria in beverages were Anaerocolumna and Ralstonia, while in grains Liquorilactobacillusdominated, with lower levels of Leuconostoc and Oenococcus.